Молодежь в общественных пространствах города - Устинова, Марина Дмитриевна (Сибирские исторические исследования)
Рец. на кн.: Walther, Andreas; Batsleer, Janet; Loncle, Patricia; Pohl, Axel (eds.) Young People and the Struggle for Participation. Contested Practices, Power and Pedagogies in Public Spaces. London: Routledge, 2020. DOI: 10.4324/9780429432095